Phytochemicals, Antioxidant and Antifungal Properties of Acorus calamus, Curcuma mangga, and Allium sativum - Muchtaromah, Bayyinatul; Ahmad, Mujahidin; S, Emy Koestanti; A, Yuni Ma’rifatul; A, Velayati Labone (KnE Life Sciences, 2017)
The purpose of this study to determine the content of phytochemicals, antioxidant and antifungal properties of the combination of Acorus calamus, Curcuma mangga, and Allium sativum. This research was descriptive qualitative, extractions were done by maceration method with ethanol with 3 different combinations (C1, C2 and C3). Phytochemical test reagent included 4 kinds of test, namely: alkaloids, flavonoids, triterpenoids, saponins and tannins. As for the antioxidant test, the method used was DPPH. The concentration used at 25, 50, 100, 200, and 400 ppm. As for the antifungal test conducted on Candida albicans with Kirby-Bauer disc methods with a concentration of 100%, followed by the MIC and MBC test with a concentration of 50%, 25%, 12.5%, 6.25%, 3.13%, 1.56%, 0.78% and 0.39%. Phytochemical test results indicated the presence of the alkaloids, flavonoids and triterpenoids compounds in 3 different combinations (C1, C2 and C3). The highest antioxidant levels founded in C1 (61.75) followed by C3 (47.94) and the lowest levels founded in C2 (42.76). The antifungal test showed the inhibitory zone against C. albicans. The highest inhibitory zone was found in C1 at 5.44 ± 1.78 mm (medium category), followed by C2 at 4.08 ± 0.86 mm (medium category), and C3 at 3.05 ± 0.23 mm (medium category). As for the minimum inhibitory concentration (MIC) value got on the concentration of 0:39% and minimum fungisidal concentration (MFC) values were at a concentration of 0.78%. Key word: Acorus calamu, Allium sativum, Curcuma manga, Antioxidant, antifungal, Candida albicans